An Integrated Analysis of Fluticasone Furoate/Vilanterol (FF/VI) Versus FF Safety Data Across Phase II and III Asthma Studies. Issue 1 (June 2016) - Busse, William; Andersen, Leslie; Frith, Lucy; Harvey, Catherine; Jacques, Loretta
Abstract Introduction An integrated analysis was performed using safety data from 18 randomized, parallel-group studies from the fluticasone furoate/vilanterol (FF/VI) GSK asthma clinical study program. Efficacy data from four pivotal studies were also analyzed. Methods Data were integrated from 18 Phase IIb and Phase III clinical studies. Key treatment arms were FF/VI 200/25 µg, FF/VI 100/25 µg, FF 200 µg, FF 100 µg, VI [with inhaled corticosteroids (ICSs)] 25 µg, and placebo. Safety endpoints included adverse events (AEs), AEs of special interest, 24-h urinary cortisol, vital signs, electrocardiograms, and asthma composite endpoints (defined as asthma-related hospitalizations, intubations, or death). Key efficacy endpoints included lung function assessments and symptomatic measures. Results In total, 7229 patients were randomized to one of six key treatment groups. The most frequently experienced AEs across key treatment groups were headache, nasopharyngitis, and upper respiratory tract infection. A greater incidence of local steroid effects was reported with FF-containing treatment groups versus placebo. No statistically significant difference was observed in asthma composite endpoint (asthma-related hospitalizations, intubations, or death) analysis of all FF/VI doses versus all ICS doses. A statistically significant difference in trough forced expiratory volume in one second (FEV1 ), 0–24 h weighted mean FEV1, and rescue-free and symptom-free 24 h periods was reported between FF/VI and FF treatment groups in all studies except one (NCT01165138). Conclusion There was no evidence of an increased safety risk associated with FF/VI versus FF, VI, or placebo. FF/VI improved lung function and symptomatic endpoints versus FF alone. These data support the positive benefit:risk ratio of FF/VI versus FF alone and of having two approved FF/VI strengths to ensure appropriate treatment for patients with different asthma severity. Funding GSK.